Major depressive disorder after heart transplantation with partial response to antidepressant therapy and remission with aripiprazole augmentation: A case report - Toshinori Nakamura; Yuta Kuraishi; Dai Ohya; Kazuhiro Kimura; Daimei Sasayama; Shinsuke Washizuka (Wiley, 2024)
Abstract The incidence of major depressive disorder (MDD) after heart transplantation is high; however, there are no reports on treatment options when antidepressant therapy fails to improve the condition. We herein report on the case of a woman with MDD after heart transplantation who partially improved with antidepressant treatment but continued to have a loss of appetite. Augmentation treatment with aripiprazole improved her appetite, and her MDD went into remission. When antidepressant treatment is not sufficiently effective for MDD after heart transplantation, augmentation treatment with antipsychotics, such as aripiprazole, should be considered.